Effectiveness of RSI and Bollinger Bands in Identifying Buy and Sell Signals - Irwansyah, Nur Fadiyah Ifa Putri; Jaya, Asri; Nasrullah, Nasrullah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
This research compares the accuracy levels of the RSI indicator and Bollinger Bands and evaluates their combination in determining buy and sell signals for stocks in IDXMESBUMN17. This index comprises 17 State-Owned Enterprises (SOEs) that comply with sharia principles. The study population includes all companies listed in IDXMESBUMN17, with the sample selected through purposive sampling based on three criteria, resulting in seven issuers: ANTM, ELSA, PTPP, SMBR, TLKM, WEGE, and WTON. Data was collected using documentation techniques, capturing buy and sell movements from chart intersections generated between January and December 2023 using Profits Anywhere software. The Mann-Whitney test was employed for data analysis, revealing a significant difference in accuracy levels. The RSI indicator achieved an accuracy of 65.6%, Bollinger Bands 70.2%, and their combination 87.5%. These findings indicate that combining RSI and Bollinger Bands provides a more accurate method for identifying buy and sell signals than using either indicator alone. This suggests that investors can enhance their trading decisions by integrating both indicators to optimize stock market strategies.